Safety and Immunogenicity of an Anti–Zika Virus DNA Vaccine - Tebas, Pablo; Roberts, Christine C; Muthumani, Kar; Reuschel, Emma L; Kudchodkar, Sagar B; Zaidi, Faraz I; White, Scott; Khan, Amir S; Racine, Trina; Choi, Hyeree; Boyer, Jean; Park, Young K; et al. (The New England journal of medicine, 2021)
There are no known specific therapies or vaccines to treat or prevent Zika virus infection. In this report, encouraging data are presented from a phase 1 study of a DNA vaccine against ZIKV infection.